Impact of Mekong River biodiversity on the food culture of women and children in Prey Veng, Cambodia - Nurhasan, M.; Sok, D.; Thilsted, Shakuntala H.; Nguon, S.; James, D.; Ritz, C.; Sok, S.; Chhoun, C.; Roos, N. (Michigan State University Press, 2022)
Situated in the heart of the Mekong River basin, the biodiversity of Cambodian freshwaters is high, with around 475 fish species. Fisheries have shaped Cambodian culture, including traditional diets. Fish and other aquatic animals are the main and culturally preferred animal-source foods in a population vulnerable to food insecurity and malnutrition. The food culture of consuming fish with the bones and head is nutritionally valuable, providing high-quality nutrients. The objective of this study was to assess the consumption of fish and other aquatic animals among mothers and their young children, with details on species, types of processing, and parts consumed. We interviewed 100 mothers in Prey Veng Province, Cambodia, on fish and other aquatic animals consumed by themselves and their children (one child per mother) during the preceding rainy season. To support recall of fish consumption, we used 157 cards with pictures of fish and other aquatic animal species and 11 cards with processed fish. Our results showed that species diversity in mothers’ diets was higher than that of their children; on average, mothers and children consumed 69 and 14 species of fish, eight and one species of other aquatic animals, respectively, in the preceding rainy season. On average, mothers reported they knew of 113 fish species and 14 other species available in their surrounding environments. Consuming fish with the head and bones is common among mothers but not children. Our study showed that the rich biodiversity of aquatic animals in the Mekong River is reflected in the food culture of mothers, but not in children. Consequently, children in their most critical period, do not harness the nutritional benefits from the rich aquatic biodiversity. We suggest policymakers recommend feeding young children with a larger diversity of aquatic animals and promoting fish processing to allow young children to benefit from the rich aquatic diversity and their nutrient-rich parts.